Principle of Primal Order in the ritual healing techniques in the community of San Rafael (Andean Philosophy) - María José Rivera Ullauri (Universidad de Antioquía, 2015)
This essay examines, using philosophical delimitation, along with observation and fieldwork, how an important element of Andean philosophy, the Principle of Primal Order, is manifested in the ritual healing techniques used in the community of San Rafael, Ecuador. Because Andean philosophy exists mainly in the real praxis rather than in graphology, our thesis is that the characteristics of the Principle of Primal Order exists in these specific practices. In the final section we examine the epistemological relatedness of the ritual healing techniques in the community of San Rafael.